Energy and protein utilisation by broiler chickens fed diets containing cottonseed meal and supplemented with a composite enzyme product. Issue 4 (3rd July 2020) - Abdallh, M. E.; Ahiwe, E. U.; Musigwa, S.; Chang'a, E. P.; Al-Qahtani, M.; Cadogan, D. J.; Iji, P. A.
ABSTRACT: 1. The present study examined the potential of new-generation microbial enzymes to improve the utilisation of energy and protein of cottonseed meal (CSM)-containing diets, with the aim of increasing its inclusion level in broiler chickens diets. 2. Four hundred and eighty, one-day-old Ross 308 male broilers were used to assess the utilisation of energy and protein by broiler chickens fed diets containing four graded levels of CSM – none, low (4, 8, 12%), medium (5, 10, 15%) or high (6, 12, 18%) in the starter, grower, and finisher phases, respectively, supplemented with 100 mg/kg of a composite enzyme product (xylanase and β-glucanase). 3. Inclusion of CSM improved (P < 0.01) apparent metabolisable energy (AME), with further improvement (P < 0.001) seen in the enzyme-supplemented diets. Inclusion of CSM reduced (P = 0.002) the metabolisable energy intake (MEI), but this was increased (P < 0.05) with enzyme supplementation. 4. Enzyme addition increased (P < 0.001) the net energy of production (NEp), while heat production (HP) decreased (P < 0.001) with CSM inclusion. More energy was retained as fat (P < 0.05) and protein in birds fed diets with the enzyme, but this was reduced (P < 0.029) by CSM. 5. There was an increase (P < 0.05) in efficiencies of ME use for energy, lipid and protein retention, with higher CSM levels. The enzyme improved (P < 0.013) efficiency of ME use for lipid retention. 6. Feeding diets containing CSM to the broilers enhanced (P < 0.05) protein intake (PI) and protein efficiency ratio (PER). Positive effects (P < 0.05) of enzyme were observed on protein gain (PG) and net protein utilisation (NPU). 7. Results obtained from this study suggested that nutrient utilisation of diets containing CSM by broiler chickens can be improved by enzyme supplementation.